2010
DOI: 10.1103/physrevb.82.104511
|View full text |Cite
|
Sign up to set email alerts
|

Vortex clusters and multiquanta flux lattices in thin films of anisotropic superconductors

Abstract: The distinctive features of equilibrium vortex structures in thin films of anisotropic superconductors in tilted magnetic fields are studied for the limits of moderate and strong anisotropy. The energetically favorable shape of isolated vortex lines is found in the framework of two particular models describing these limiting cases: London theory with an anisotropic mass tensor and London-type model for a stack of Josephson-decoupled superconducting layers. The increase of the field tilting is shown to result i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 26 publications
4
29
0
Order By: Relevance
“…Recently, the GL method was re-derived in the context of superfluid ultracold Fermi gases [2,3,4,5]. The GL approach was also applied to explain the phenomenon of the "1.5-type" superconductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the GL method was re-derived in the context of superfluid ultracold Fermi gases [2,3,4,5]. The GL approach was also applied to explain the phenomenon of the "1.5-type" superconductivity.…”
Section: Introductionmentioning
confidence: 99%
“…One can observe an interplay between the long-range attractive and the repulsive forces between two zigzag deformed PV stacks, similar to the one between two tilted vortices in layered [8] or anisotropic [10] SC films. Certainly, in a bulk sample (D → ∞) the Pearl term in (18) vanishes, and at long distances the dominant interaction between the zigzag PV lines is an attraction [16].…”
Section: Interaction Potential Of Zigzag Vorticesmentioning
confidence: 99%
“…When the magnetic field increases, these "molecules" start to build vortex lattice. In fact, the particularity of the intervortex interaction results in the emergence of the flux structures with different number of vortices per unit cell [10].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we consider the long-range Pearl repulsion as a candidate [33,34]. It is produced by the stray field near the surface outside the samples and should be important for thin samples [25,35]. Second, the chainlike clustering structure of vortices in superconductors is indicative of intervortex attraction.…”
Section: Introductionmentioning
confidence: 99%
“…(I-II) For moderately anisotropic superconductors like YB-CO, it has been demonstrated that the field changes sign in some local regions in the plane perpendicular to the flux-line axis under a tilted magnetic field [24][25][26], leading to intervortex attraction in those regions. (IV) For the layered superconductors with very weak inter-layer coupling, the Josephson Vortices (JV) will appear at much lower field near H c1 [25]. The PV are attracted and trapped by JV and thus form chains [27,28].…”
Section: Introductionmentioning
confidence: 99%